Differentiation of the concentration of heavy metals and persistent organic pollutants in lake sediments depending on the catchment management (Lake Gopło case study) - Juśkiewicz, Włodzimierz Waldemar; Marszelewski, Włodzimierz; Tylmann, Wojciech (Bulletin of Geography. Physical Geography Series, 2015)
This paper presents the results of the study on the concentration of heavy metals and persistent organic pollutants (POPs), including PAHs and PCBs, in the bottom sediments of Lake Gopło. This lake is significantly elongated (about 25 km); its longitudinal profile is diversified, and there are deeps and thresholds impeding the flow of water. The shoreline is varied, which is characteristic of tunnel valley lakes. The catchment has a typical agricultural character with a point arrangement of industrial centres. The analysis of the diversity of the concentration of heavy metals and POPs was based on 37 samples from two representative cores: one collected in the northern part of the lake, the catchment of which shows an industrial character, and the second one in the southern part where the catchment is agricultural in character. In the sediments, the content of the following heavy metals was analysed: Cu, Pb, Cd, Zn, Ni, Cr, Hg and As, as well as PAHs and PCBs. The sediment age was determined by the 210Pb dating method. In order to assess the contamination level of the bottom sediments with heavy metals, the contamination factor (CF) and degree of contamination (DC) were calculated. Moreover, the impact of the changes in the catchment’s land use over the past 100 years was determined. The results showed that the sediments from the industrial part of the lake significantly exceed the geochemical background for both the heavy metals from the group identified as industrial pollution and from the group of agricultural pollutants. The southern core shows only a slight increase in the amount of pollution from the agricultural group, lack of industrial pollution and a low degree of contamination. A slight increase in persistent organic pollutants is also recorded, without any apparent effect on the state of the deposited sediment. The 210PB dating enabled the main stages of human impact to be determined: the pre-industrial revolution, from the beginning of industrialisation to the 1950s, intensive human impact from the 1960s to the 1980s, and a gradual decrease in the human impact starting from the 1990s. In addition, attention was paid to the changing sedimentation rate.